Investigation on improved water-loaded diagonal horn applicators for hyperthermia - Singh S.; Singh S.P. (My University, 2025)
This paper describes simulation, theoretical, and/or experimental studies of specific absorption rate (SAR) distribution in biological phantom (muscle)/tri-layered bio-media without and with irregular-shaped tumors in direct contact with improved water-loaded metal diagonal horns designed at 2450 and 915 MHz. Further, thermal simulation results based on Pennes’ bio-heat equation are also provided for each of the proposed applicators, which is in direct contact with realistic tri-layered bio-media without and with irregular-shaped tumor embedded within the muscle layer. The proposed horns are improved versions of the respective conventional metal diagonal horns in which the aperture fields, which are modified by introducing four conducting pins at appropriate locations near each antenna aperture, correspond to fundamental and higher order modes. The theoretical aperture field distributions of the proposed horns designed at 2450 and 915 MHz are compared with the corresponding simulated ones. Further, the theoretical SAR parameters (penetration depth (PD) and effective field size (EFS)) in the phantom muscle medium due to the proposed horns designed at 2450 and 915 MHz are compared with the corresponding simulated and/or experimental results as well as with those obtained due to the corresponding conventional horns of identical dimensions. Moreover, effects on PD, EFS/EFS25, and temperature distribution profiles due to presence of irregular-shaped tumor in the tri-layered bio-media at 2450 and 915 MHz are also investigated. It is demonstrated that desired temperature range 41–45 °C can be achieved and maintained for 60 min with input power of 4/10 W at the frequencies of 2450/915 MHz for treating superficial tumors. © 2016 Informa UK Limited, trading as Taylor & Francis Group.